Melanoacanthoma: Uncommon presentation of an uncommon condition - Resham J Vasani; Swapna S Khatu (Wolters Kluwer Medknow Publications, 2013)
Melanoacanthoma is very rare variant of seborrheic keratosis presenting as a deeply pigmented benign proliferation of melanocytes and keratinocytes usually presenting over the head, neck and trunk of elderly people. A sixty-two-years-old male was presented with a solitary slow growing asymptomatic hyperpigmented verrucous outgrowth with cerebriform surface measuring 15 cm by 8 cm present over the left inguinal region extending on to the scrotum since past 8 years. There was no associated lymphadenopathy. The histopathology revealed hyperkeratosis, papillomatosis, acanthosis with presence of melanocytes at all levels of epidermis with abundant melanin giving the diagnosis of melanoacanthoma. The patient further underwent surgical excision of the lesion. The case is being reported for its rarity, unusual location, massive size and clinical resemblance to a verrucous carcinoma.